Eating behaviour and its associations with overweight among nurses on shift duty in teaching hospital - Hng, Siew Hong; Maziah AM,; L, Evica HS; Liew, QW (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Overweight and obesity have become a global concern and estimated with more than 1.9 billion adults worldwide were overweight and more than 650 million were obese in 2016. Nurses in Malaysia were no exception to overweight and obesity. This research was conducted with the aim to identify the prevalence of overweight among nurses on shift duty in a teaching hospital and to understand the relationship between abnormal eating behavior and body mass index. A total of 280 respondents participated in this research and Dutch Eating Behavior Questionnaire was used. Body Mass Index (BMI) score was categorized according to Clinical Practice Guidelines 2004. Results showed that 68.5% of the nurses were either overweight (37.1%) or obese (31.4%). The nurses’ BMI does not showed any association with socio-demographic data except age (r=0.156). As age increases, the nurses’ BMI also increase. This research also showed that there was no association between emotional and external eating behavior to BMI. However, there was a statistically significant differences in BMI for restraint eating (F=6.056, p=0.003). In conclusion, restraint eating behavior was the most practiced form of eating behavior in an attempt to achieve the ideal body weight but unfortunately lead to overweight among the nurses. Overweight or obese nurses will have a negative impression to the society and even reduce their confidence towards nurses’ health education. Overweight or obesity also ruined the nurses’ working performance and quality of care for patients. This issue requires immediate action and interventions to promote healthy lifestyles and eating habits among nurses should be conducted in the hospital.